IMPACT OF WHO LABOR CARE GUIDE ON REDUCING CESAREAN SECTIONS AND ITS USABILITY BY HEALTHCARE PROFESSIONALS AT A TERTIARY CARE HOSPITAL, KARACHI. (Journal of Medical & Health Sciences Review, 2025)
Objective: To evaluate the impact of the WHO Labour Care Guide (LCG) on reducing primary caesarean section rates, improving labor outcomes, and determining its usability among healthcare providers in a tertiary care hospital in Karachi.Methods: This open-label randomized controlled trial conducted at Department of Gynecology and Obstetrics of Jinnah Postgraduate Medical Centre, Karachi from September, 2024 to February, 2025. The Study included 284 term pregnant women who were randomly assigned to either LCG-based monitoring or standard care using the modified partograph. Baseline characteristics were comparable between groups. Primary outcome was mode of delivery. Secondary outcomes included duration of active labor, maternal complications, neonatal outcomes, and provider acceptability assessed through a structured Likert-scale questionnaire.Results: The caesarean rate was significantly lower in the LCG group (12.7%) compared with standard care (23.9%). Active labor duration was shorter with LCG monitoring (5.1 ± 1.7 vs. 6.0 ± 1.9 hours). Maternal and neonatal outcomes, including postpartum hemorrhage, puerperal sepsis, Apgar scores, and NICU admissions, were similar between groups. Most healthcare providers reported high ease-of-use and satisfaction with the LCG.Conclusion: Use of the WHO Labour Care Guide resulted in fewer caesarean deliveries, more efficient labor progress, and high provider acceptability without compromising maternal or neonatal safety. Incorporating the LCG into routine intrapartum care may support evidence-based labor management in high-volume tertiary settings.